2012
DOI: 10.1097/ajp.0b013e31822be973
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Music Intervention in the Management of Chronic Pain

Abstract: These results confirm the value of music intervention to the management of chronic pain and anxiety/depression. This music intervention method appears to be useful in managing chronic pain as it enables a significant reduction in the consumption of medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
23

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 27 publications
1
72
0
23
Order By: Relevance
“…The study by Valet and associates 28 also confirmed the opinion of Cook 29 that music therapy could divert patients' attention from fear of pain and that is the reason why so many clinical research studies had reported music therapy could be widely used in both acute pain and chronic pain treatment. 30,31 In addition, some studies even reported that music intervention could reduce the dose of analgesic and sedation drugs in invasive procedures. 23,32 Careful consideration is needed when selecting music for the purpose of releasing both pain and anxiety.…”
Section: Fig 1 Box Plots Of Pain Score (Visual Analog Scalementioning
confidence: 99%
“…The study by Valet and associates 28 also confirmed the opinion of Cook 29 that music therapy could divert patients' attention from fear of pain and that is the reason why so many clinical research studies had reported music therapy could be widely used in both acute pain and chronic pain treatment. 30,31 In addition, some studies even reported that music intervention could reduce the dose of analgesic and sedation drugs in invasive procedures. 23,32 Careful consideration is needed when selecting music for the purpose of releasing both pain and anxiety.…”
Section: Fig 1 Box Plots Of Pain Score (Visual Analog Scalementioning
confidence: 99%
“…Listening to music reduces acute and chronic pain (Guétin et al, 2012; Roy et al, 2012; Korhan et al, 2013). Several studies have suggested that the analgesic effect of music (or music-induced analgesia) may be secondary to cognitive and emotional effects that arise from listening to music: distraction from the pain, pleasantness, and pleasure, memory evoked emotions and relaxation (Mitchell et al, 2006; Juslin and Västfjäll, 2008; Roy et al, 2008, 2009; Wiech and Tracey, 2009; Bernatzky et al, 2011; Salimpoor et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, distraction was associated with reduced pain intensity, unpleasantness, and pain-related activation in the brain, specifically in the "medial pain system". Valet et al [21] confirmed the opinion of Cook et al [22] that music could divert patients' attention from the fear of pain, and as such provided an explanation on why music could be considered a useful option for the treatment of acute and chronic pain [23,24]. In addition, other studies have reported that patients undergoing music therapy during invasive procedures can tolerate pain at lower analgesic or sedative doses [25,26].…”
Section: Discussionmentioning
confidence: 69%